Effect of Blended Learning Strategy on Learning Outocmes in Science among Secondary School Students - Kaur, Manpreet; Kaur, Parminder (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
Learning should be ingrained with the creation of original academic work using a thoughtful blend of techniques. The educational process has altered in the digital age to meet the needs of our "digital natives." Today, online and offline learning are employed in tandem depending on the needs and learning styles of the students. Blended learning is the result of combining various learning modalities. This approach goes beyond the typical speed, location, and style of instruction. It gives the flexibility to the education system. It is reducing all types of situational obstacles and expanding the learning environment with a wide range of novel methods, tools, and ideas. Blended learning modules were created to investigate the impact of this method on secondary school students' attitudes toward science. A quasi-experimental approach was used, with one group being the control group that received standard care and the other being the experimental group that participated in the integrated learning strategy. The t-test was used to analysed the data. It was determined that secondary school pupils' gain scores for learning outcomes in science range significantly from one another.